The Effect Of Meat Storage Of Rendang Quality - Fadhila Ramadhanti; Wiwik Gusnita (Universitas Negeri Padang, 2020)
Meat has physical properties that are easily damaged because microorganisms can grow and develop in it. Meat damage can occur physically or chemically. The way to prevent this damage is to store the meat at a low temperature. Based on the beliefs of the Minangkabau people, it is said that when making rendang, the meat used must be fresh. So that the quality of the rendang is better. In this study, the type of meat used to make rendang is divided into two, namely fresh meat and frozen meat. Frozen meat comes from fresh meat that is stored and frozen for 4 days. This study aims to compare the quality of rendang with the use of fresh meat and frozen meat. This type of research is an experiment with organoleptic test. The study was conducted in 3 repetitions with 5 limited panelists. The data obtained were analyzed using the T test (t test). The results showed that the average quality of the two rendang was almost the same. The average values of the quality of rendang using fresh and frozen meat are form, namely 3,13 and 3,2; the color of the inner flesh, namely 3,2 and 3,53; bran colors, namely 3,6 and 3,8; aroma namely 3.73; meat texture, namely 3,6 and 3,4; bran texture 3,33 and 3,4; bran flavor that is 3,8; and the taste of meat, namely 3,33 and 3,6. Based on the results of the t test, it was stated that there was no significant difference between rendang and the use of fresh meat and frozen meat for each quality tested.Keyword: Meat Storage, Rendang, Quality